A Metal-Free β-Stereoselective Synthesis of 2-Deoxy-C-arylglycosides: Synthesis of 5-Aza Analogues of Aquayamycin - Mei, Yuling; Jiang, Nan; Yang, Yu; Zhang, Wan; Qiu, Saifeng; Guo, Hong; Zhang, Jianbo (Synlett, 2021)
A convenient protocol for the β-stereoselective synthesis of 2-deoxy-C-arylglycosides has been developed. This reaction takes place in one step by using I2/Et3SiH to activate a glycosyl acetate to generate a glycosyl iodide intermediate in situ, which is captured by a naphthol; this is followed by a Fries-like O-to-C glycoside rearrangement to afford a β-C-aryl glycoside selectively. The approach is applicable to a wide range of naphthol moieties, and its utility was demonstrated in syntheses of 5-aza analogues of aquayamycin.
Keywords: glycosylation; deoxyarylglycosides; glycosyl iodides; metal-free synthesis; aquayamycin